Project Management and Engineering Research AEIPRO 2016 - Ayuso Muñoz, José Luis.; Yagüe Blanco, José Luis.; Capuz-Rizo, Salvador F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book gathers the best papers presented at the 19th International Congress on Project Management and Engineering, which was held in Granada, Spain in July 2015. It covers a range of project management and engineering contexts, including: civil engineering and urban planning, product and process engineering, environmental engineering, energy efficiency and renewable energies, rural development, information and communication technologies, safety, labour risks and ergonomics, and training in project engineering. Project management and engineering is taking on increasing importance as projects continue to grow in size, more stakeholders become involved, and environmental, organisational and technological issues become more complex. As such, this book offers a valuable resource for all professionals seeking the latest material on the changing face of project management.
Part I: Project Management -- Chapter 1. Comprehensive Reorganization of Project Management: A Case Study -- Part II: Civil Engineering, Urbanism and Urban Planning. Building and Architecture -- Chapter 2. The Dilemma of Innovation in the Construction Company: A Decade of Lessons Learned -- Part III: Product and Process Engineering and Industrial Design -- Chapter 3. Study on the Influence of Fresh White Cheese Packaging Design Variables on Users' Perception -- Chapter 4. Study, Design, Development and Construction of a Linear Tribometer for Testing Human Skin -- Chapter 5. 3D Myocardial Modelling by Computational Geometry Techniques. Analysing Performance -- Part IV: Environmental Engineering and Natural Resource Management -- Chapter 6. Study of the Energy Recovery of the Reject Materials from Municipal Solid Waste Treatment Plants in Spain -- Chapter 7. Review of Options for Solving Problems of Frazil Ice in Industrial Water Intakes -- Chapter 8. Environmental Behaviour of an Element ofthe Construction Sector -- Chapter 9. Identification and Measurement of Complementarity Variables in Strategic Projects of Water Irrigation from the Sustainability Practices. Case: Republic of Ecuador -- Part V: Energy Efficiency and Renewable Energies -- Chapter 10. Aging Model for Re-used Electric Vehicle Batteries in Second Life Stationary Applications -- Chapter 11.Assessing the Energy Saving Potential for Building Stock and Choice of Rehabilitation Strategy by a Multicriteria System -- Chapter 12. Adapting Buildings to the Current CTE-DB-HE: A Single-family Housing Development in Logroño (La Rioja) -- Chapter 13. Geographic Information System for Optimization and Integration of Photovoltaic Solar Energy in Agricultural Areas with Energy Deficiency and Water Scarcity -- Part VI: Rural Development and Development Co-Operation Projects -- Chapter 14. Guadua angustifolia as a Structural Material for Greenhouse Design -- Part VII: IT and Communications. Software Engineering -- Chapter 15.Evaluation of the State of Cutting Tools According to Its Texture Using LOSIB and LBP Variants -- Part VIII: Safety, Labour Risks and Ergonomics -- Chapter 16.SAFEBUS: A New Active Safety System for Pedestrian Detection in Public Passenger Buses -- Part IX: Training in Project Engineering -- Chapter 17. Implementation of BIM in the subject Technical Industrial Projects - Degree in Industrial Technologies Engineering - University of Valladolid -- Chapter 18. Technological Immersion in Industrial Engineering for a Project Management Course to Develop Dual Use Technology -- Chapter 19. Quantitative and Qualitative Analysis of Project-based Learning to Acquire Competencies in Project Management. .
Keywords: Industrial engineering; Production engineering; Project management; Industrial organization; Industrial and Production Engineering; Project Management; Industrial Organization